(untitled) (Journal of Plant Disease Sciences, 2026)
Necrosis caused by (TSV) is an emerging disease in cotton crop, Tobacco streak virus particularly in Central and Southern India. A study was conducted to investigate the characteristics of TSV) infecting cotton, with a focus on its symptomology, particle morphology, host range and screening of cotton genotypes against the virus. The virus was reported to infect all foliar parts cotton plant. Characteristic symptoms caused by the virus included necrotic streaks on leaves and stems, rosetting, square drying and stunted growth. Transmission Electron Microscopy studies using leaf dip preparation of the virus revealed typical spherical TSV particles measuring 28-30 nm in diameter. To identify the host plants of the virus, host range studies were carried out under glasshouse conditions. Eleven plants spp. belonging to different families were artificially inoculated with virus sap. identified susceptibility in , , , Vigna unguiculata Cajanus cajan Vigna mungo Arachis hypogaea Helianthus annus Abelmoschus esculentus Capsicum annum Guizotia , , , and abyssinica Glycine max Cicer arietinum Lycopersicon esculentum Sesbania while , , , bispinosa Solanum melongena Parthenium hysterophorus , and were non-hosts. Screening of cotton cultivars revealed that 11 germplasm lines were immune, 27 resistant, 12 moderately resistant, while three germplasm lines were moderately susceptible and two were susceptible to the TSV under natural field condition.